Analisis Penerapan Akuntansi Berdasarkan SAK EMKM Pada UMKM Dwi Loundry - Imawan, Amrizal; Mas’adah, Ninik; Safitri, Maya; Fadhil, Faiz Abdillah (SUSTAINABLE, 2023)
The aim of this research is to analyze the suitability of implementing accounting based on SAK EMKM in Dwi Loundry MSMEs. This research was conducted using a qualitative method with a case study approach and the application of recording financial reports based on SAK EMKM using primary and secondary data taken from the Dwi Loundry business. Data collection techniques in this research used observation, interview and documentation techniques and the analysis techniques used were data reduction, data presentation and drawing conclusions. Based on data analysis, the research results show that the Dwi Loundry business has implemented accounting but the recording of financial reports is still done manually and is very simple and its implementation does not follow the provisions in SAK EMKM. The financial report prepared by the Dwi Loundry business is only a profit and loss report, while the financial position report and notes to the financial report do not yet exist. The obstacles that cause SAK EMKM not to be implemented in the Dwi Loundry business are time constraints and not knowing and understanding the preparation of financial reports based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). Keywords: Financial Reports, SAK EMKM, and UMKM